1989
DOI: 10.1002/hlca.19890720631
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements of Radical Cations of [2.2]Paracyclophanes and of a bridged [14]annulene to those of pyrenes: An ESR and ENDOR study

Abstract: ESR and ENDOR studies have been carried out on the radical cations obtained consecutively by reaction of rrans-lob, 10c-dimethyl-lob, 10c-dihydropyrene (4) with AICI, in CH,CI,. The primarily formed 4' rearranges at 253 K to the radical cation(s) of 1.6-(5a) and/or 1,8-dimethylpyrene (5b). At 323 K, the spectra of 5a'/5b' are replaced by that of the highly persistent radical cation of 1,3,6&tetramethylpyrene (6). Surprisingly, 6' is also the only observable paramagnetic product resulting from a treatment of 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Cyclophanes, which consist of two benzene rings connected by multiple alkyl chains, have attracted interest of researchers for years because of interesting properties resulting from the transannular π–π interaction of benzene rings fixed at close proximity. One of these interesting properties is good electron donor ability, which enables charge transfer (CT) complex formation with electron acceptors. Especially, [3 n ]­cyclophanes, in which benzene rings are connected by propyl chains, exhibit better donor ability than [2 n ]­cyclophanes possessing ethyl chains because of reduced strain. It has been reported that both the radical cations and radical anions of cyclophanes are highly stabilized by charge resonance interactions. …”
Section: Introductionmentioning
confidence: 99%
“…Cyclophanes, which consist of two benzene rings connected by multiple alkyl chains, have attracted interest of researchers for years because of interesting properties resulting from the transannular π–π interaction of benzene rings fixed at close proximity. One of these interesting properties is good electron donor ability, which enables charge transfer (CT) complex formation with electron acceptors. Especially, [3 n ]­cyclophanes, in which benzene rings are connected by propyl chains, exhibit better donor ability than [2 n ]­cyclophanes possessing ethyl chains because of reduced strain. It has been reported that both the radical cations and radical anions of cyclophanes are highly stabilized by charge resonance interactions. …”
Section: Introductionmentioning
confidence: 99%